Journey to Munich : a Maisie Dobbs novel - Winspear, Jacqueline, 1955- (Winspear, Jacqueline, 1955- Maisie Dobbs novel, 2016)
It's early 1938, and Maisie Dobbs is back in England. On a fine yet chilly morning, as she walks towards Fitzroy Square--a place of many memories--she is intercepted by Brian Huntley and Robert MacFarlane of the Secret Service. The German government has agreed to release a British subject from prison, but only if he is handed over to a family member. Because the man's wife is bedridden and his daughter has been killed in an accident, the Secret Service wants Maisie--who bears a striking resemblance to the daughter--to retrieve the man from Dachau, on the outskirts of Munich.